2021
DOI: 10.4038/jas.v16i03.9475
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' Willingness to Pay for Organic Fresh Milk in Saudi Arabia

Abstract: Purpose: Consumption of organic food among consumers in Saudi Arabia has increased in recent times due to increased awareness of health benefits of organic food. The purpose of this paper is to estimate the average amount a consumer is willing to pay in Saudi Arabia for fresh organic milk.Research Method: This paper used the Double Bounded Dichotomous Choice (DBDC) model to identify key determinants of consumers' willingness to pay (WTP) for fresh organic milk. Findings:The results showed that organic product … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…According to Dimitri and Dettmann's [51] research, consumers with lower incomes are less likely to purchase organic milk. In another study, Almarri and Al-Mahishi [44] observed that consumers' willingness to pay for organic milk increased as their incomes did in Arabia. Bahsi et al [52] also state that income has a significant impact on consumers' willingness to pay more for organic milk, which indicates similar results.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…According to Dimitri and Dettmann's [51] research, consumers with lower incomes are less likely to purchase organic milk. In another study, Almarri and Al-Mahishi [44] observed that consumers' willingness to pay for organic milk increased as their incomes did in Arabia. Bahsi et al [52] also state that income has a significant impact on consumers' willingness to pay more for organic milk, which indicates similar results.…”
Section: Discussionmentioning
confidence: 96%
“…However, the number of consumer studies conducted specifically on organic milk and dairy products is quite limited in Türkiye. Studies show that factors such as price and habit information [34][35][36], health [37][38][39][40][41][42][43][44], taste and income [45][46][47][48], environmental concern [49], knowledge of organic products [25], income [29,33,[50][51][52], content [53,54], food safety [33,55], production technique and regional origin [56], and high animal welfare [47] have the highest impact on organic milk consumption.…”
Section: Introductionmentioning
confidence: 99%